The Legality of Smart Contract in the Perspectives of Indonesian Law and Islamic Law - Munawar, Munawar (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This study aims to determine the legal status of smart contracts from the perspective of Indonesian law and Islamic law through a comprehensive literature review. The revolution of the internet and smartphones has changed human life, as happens in smart contracts. This difference in character between smart and conventional contracts has not been fully anticipated by applicable law. That is why the urgency of fiqh renewal or reform of the law in the cyberspace era. Although smart contracts are still in their infancy, and there are still many critical issues that need to be resolved, the results of the literature research show that the smart contract has fulfilled the principles in the agreement/contract in Islamic law. According to the ITE Law, a smart contract can be interpreted as an agreement referred to in Article 1313 of the Civil Code, "an act where one person binds himself to one or more other people". Although this study is not sufficient, this needs to be elaborated from the perspective of Indonesian law. The most important things in smart contracts to comply with the Islamic law are: the sequence of processes in the smart contract must comply with Islamic law, the object being transacted must be halal, the perpetrators have complied with the provisions of the Islamic law, fixed price during the contract period and the number of parties involved in the contract may increase over time.